Clinton family papers - Clinton, George, 1739-1812.; Clinton, George, 1771-1809.; Clinton, James, 1733-1812.
Chiefly correspondence (mainly transcripts and drafts) of the elder George Clinton and James Clinton relating to military engagements during the Revolution, drafting of the Articles of Confederation by the Continental Congress, and land transactions in New York; orderly book (1779) of James Clinton containing orders given during the expedition against the Iroquois; and various commissions, land grants, and resolves. Correspondents include Horatio Gates, the Marquis de Lafayette, Philip John Schuyler, Ambrose Spencer, and George Washington.
Microfilm edition available, in part
Microfilm produced from materials in the Manuscript Division.
In part, photocopies and typewritten transcripts.
Family members represented include George Clinton (1739-1812), U.S. vice president, delegate to the Continental Congress, and governor of New York; his brother, James Clinton (1733-1812), Continental army officer and public official; and George Clinton's son, George Clinton (1771-1809), U.S. representative from New York.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Collection material in English.
Keywords: Clinton family; Gates, Horatio, -- 1728-1806 -- Correspondence; Lafayette, Marie Joseph Paul Yves Roch Gilbert du Motier, -- marquis de, -- 1757-1834 -- Correspondence; Schuyler, Philip John, -- 1733-1804 -- Correspondence; Spencer, Ambrose, -- 1765-1848 -- Correspondence; Washington, George, -- 1732-1799 -- Correspondence; United States; United States. -- Continental Army; United States. -- Continental Congress; Iroquois Indians; Indians of North America -- New York (State); Indians of North America -- Wars -- 1775-1783.; Land grants -- New York (State); Land tenure -- New York (State); New York (State) -- History -- Revolution, 1775-1783.; New York (State) -- Politics and government -- 1783-1865.; United States -- History -- Revolution, 1775-1783 -- Campaigns; United States -- History -- Confederation, 1783-1789.; United States -- Politics and government -- 1783-1809.; Army officers; Governors -- New York (State); Public officials